Does the quality of training programs matter? Evidence from bidding processes data - Alberto Chong; Jose Galdo (Institute for the Study of Labor (IZA), 2006)
We estimate the effect of training quality on earnings using a Peruvian program, which targets disadvantaged youths. The identification of causal effects is possible because of two attractive features in the data. First, selection of training courses is based on public bidding processes that assign standardized scores to multiple proxies for quality. Second, the evaluation framework allows for the identification and comparison of individuals in treatment and comparison groups six, 12, and 18 months after the program. Using difference-in-differences kernel matching methods, we find that individuals attending high-quality training courses have higher average and marginal treatment impacts. External validity was assessed by using five different calls over a nine-year period.
Keywords: I38; H43; C13; C14; 330; training; quality; earnings; bidding; matching methods